Phenomenology of Children’s Reactions to G-Rated Animations and Its Educational Implications for Enhancing Moral Inquiry - Gourkani, Fariba; Ghaedi, Yahya; Hoseini, Afzalossadat (Iranian Journal of Educational Sociology, 2026)
Purpose: This study aimed to phenomenologically explore children’s reactions to G-rated animations and extract their educational implications for producing children’s media content that promotes moral inquiry. Methods and Materials: The research employed a qualitative phenomenological design with an interpretive and inductive approach. The study was developmental–applied in purpose and cross-sectional in timing. Participants included two groups: ten children aged six to nine years, selected through purposive sampling, and fifteen experts in education, psychology, and children’s art. Data were collected using observation and semi-structured interviews with children, followed by a focus group discussion with experts. Data analysis was conducted through Colaizzi’s seven-step phenomenological method and thematic analysis using MAXQDA software, enabling the identification of both children’s experiential meanings and experts’ educational inferences. Findings: Children’s reactions revealed complex moral, emotional, and cognitive engagement with the animated content. Participants displayed empathy toward animated characters, moral reasoning about fairness and justice, and critical thinking regarding narrative outcomes. Their affective responses showed awareness of ethical dualities—good versus bad and acceptance versus prejudice. The phenomenological analysis identified central themes such as identity discovery, empathy, courage, acceptance of differences, friendship, emotional regulation, and environmental concern. Expert panel discussions emphasized the educational potential of animations to cultivate moral reasoning, critical inquiry, and social awareness in children when guided by reflective dialogue and pedagogical framing. Conclusion: G-rated animations serve as effective moral and educational tools that facilitate children’s moral inquiry, empathy, and cognitive development through imaginative engagement. Integrating phenomenological insights into animation production and educational practice can strengthen children’s ethical understanding, emotional literacy, and reflective thinking.